Fruit Morphology, Antioxidant Activity, Total Phenolic and Flavonoid Contents of Salacca zalacca (Gaertner) Voss by Applications of Goat Manures and Bacillus velezensis B-27 - Haviah Hafidhotul Ilmiah; Endang Sulistyaningsih; Tri Joko (Caraka Tani: Journal of Sustainable Agriculture, 2021)
Snake fruit (Salacca zalacca (Gaertner) Voss) is one of indigenous fruits from Southeast Asia that has been consumed for its antioxidant contents. Improving the fruit quality might increase its benefits for human health. This study aims to analyze fruit morphology, antioxidant activity, total phenolic and flavonoid contents of the fruit applied with goat manures and Bacillus velezensis B-27. The research used two-factor Randomized Complete Block Design (RCBD) with three blocks as replications. The first factor is the level of goat manure application i.e. 0 kg plant-1, 5 kg plant-1 and 10 kg plant-1, while the second factor is the bacteria application i.e. applied with Bacillus velezensis B-27 and without Bacillus velezensis B-27. The research was conducted in June until December 2019 at Turi, Sleman, Yogyakarta, Indonesia. Fruit length, diameter and shape were measured as morphology parameters. Antioxidant activities were measured using 2,2-Diphenyl-1-picrylhydrazyl, whereas flavonoid and phenolic contents were determined by the aluminium-chloride colorimetric and Folin-Ciocalteu methods, respectively. Means of each parameter were analyzed using ANOVA, continued with the Tukey’s HSD test at a 5% significance level. The result showed that the application of 10 kg goat manure per plant with bacteria increased the fruit length (76.78 mm) and the diameter (62.72 mm). Addition of 10 kg goat manure per-plant combined with Bacillus velezensis B-27 gave the highest antioxidant (IC50 of 37.83 µg.mL-1), flavonoid (5.35 mgGAE.100 g-1) and total phenolic contents (44 mgQE.100 g-1).